An accurate map of North America: describing and distinguishing the British, Spanish, and French dominions on this great continent, exhibiting the present seat of war, and the French encroachments, also all the West India Islands belonging to, and possessed by the several European princes and states, the whole laid down according to the latest and most authentick improvements - Bowen, Emanuel, d. 1767.;Gibson, J. (John), fl. 1750-1792.;Pownall, Thomas, 1722-1805. (Robert Sayer, 1755)
Relief shown pictorially. Shows cities and towns, trading paths, roads, and Native American settlements. Includes detailed notes, comments, and explanations. North Carolina is depicted as extending into present day Oklahoma. Tribes indicated in the North Carolina region include the Cherakees (Cherokees), Chicasaws (Chickasaws) and the Catawbas. Includes decorative illustration in top right corner. Includes 2 insets: "A particular map of Baffin and Hudson's Bay" and "The passage by land to California, discovered by Father Eusebius Francis Kino, a Jesuit, between the years 1698 and 1701 before which and for a considerable time since California has always been described in all charts & maps as an island." The map was printed from four separate copperplates, on four sheets. This map is a first edition, first issue.